IMPLEMENTASI PENGEMBANGAN ANAK USIA DINI HOLISTIK INTEGRATIF SEBAGAI STRATEGI DALAM MEMPERKUAT LAYANAN PERLINDUNGAN DAN PEMENUHAN HAK ANAK DI TK ISRIYATI SUGITO - Siti Nasekah; Nur Intan Rochmawati; Himmah Taulany; Nufitriani Kartika Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Holistic Integrative Early Childhood Education (PAUD HI) is a comprehensive and integrated service approach designed to fulfill the essential needs of early childhood. The implementation of PAUD HI does not only focus on educational aspects but also includes health, nutrition, caregiving, protection, and child welfare. This study aims to determine how the implementation of PAUD HI serves as a strategy in strengthening child protection services and fulfilling children’s rights at TK Isriyati Sugito. This research employed a qualitative approach using a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects included the principal, teachers, and related parties involved in the implementation of the PAUD HI program. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of PAUD HI at TK Isriyati Sugito has been carried out through various integrated programs, such as child-friendly learning activities, health and nutrition monitoring, collaboration Layanan with parents, and the implementation of child protection policies within the school environment. These strategies are able to strengthen protection services and ensure the fulfillment of children’s rights in aspects of growth and development, participation, and a sense of security within the school environment. Therefore, the implementation of PAUD HI becomes an effective strategy in supporting optimal child protection and the fulfillment of children’s rights. Schools are expected to continuously improve coordination with various stakeholders to ensure that the services provided are increasingly high-quality and sustainable.